TikTok, Influencers, and Price Shaping Gacoan Purchase Decisions: TikTok, Influencer, dan Pembentukan Harga dalam Pengambilan Keputusan Pembelian Gacoan - Rahmadana, Muhammad Haris; Indayani, Dra. Lilik Indayani, M.M (Indonesian Journal of Law and Economics Review, 2025)
General Background: The rapid growth of social media platforms has transformed consumer behavior, with TikTok emerging as a dominant marketing channel in Indonesia’s digital economy. Specific Background: Mie Gacoan, a popular culinary brand in East Java, utilizes TikTok and influencer collaborations to attract younger audiences and boost sales. Knowledge Gap: However, limited empirical studies have examined the combined role of TikTok, influencer credibility, and pricing strategies in shaping consumer purchase decisions in the regional culinary industry. Aims: This study investigates how TikTok marketing, influencer endorsement, and price perception contribute to consumers’ purchasing decisions for Mie Gacoan in East Java. Results: Quantitative analysis using SPSS on 100 respondents reveals that all three variables—TikTok engagement, influencer credibility, and affordable pricing—positively and significantly predict purchasing decisions. Novelty: The study provides a contextual understanding of social media-driven marketing in a local Indonesian food brand, emphasizing the synergy between digital content, influencer marketing, and price sensitivity. Implications: Findings guide marketers to optimize social media strategies, strengthen influencer partnerships, and set competitive pricing to enhance consumer engagement and purchase behavior. Highlights: TikTok, influencers, and pricing jointly shape purchase behavior. Empirical evidence from East Java’s culinary market. Offers strategic insights for digital marketing optimization. Keywords: TikTok Marketing, Influencer, Price Strategy, Consumer Decision, Digital Promotion